Lyotard and politics : a critical introduction - Sim, Stuart (Thinking politics (Edinburgh, Scotland), 2020)
Stuart Sim explores how Lyotard's brand of pragmatism can provide a focus for political theory and action in our cultural climate, especially in light of the dramatic resurgence of right-wing extremism.